Functionalized TMC and ε-CL elastomers with shape memory and self-healing properties - Chen, Siwen; Xiao, Miaomiao; Hou, Zhipeng; Li, Zhongcun; Hu, Jianshe; Guo, Jing; Chen, Jing; Yang, Liqun; Na, Quan (Frontiers in Bioengineering and Biotechnology, 2023)
Smart elastomers, which possess self-healing and shape memory capabilities, have immense potential in the field of biomedical applications.Polycarbonates and polyesters have gained widespread interest due to their remarkable biocompatibility over the last century. Nevertheless, the lack of functional versatility in conventional polyesters and polycarbonates means that they fall short of meeting the ever-evolving demands of the future. This paper introduced a new smart elastomer, named mPEG43-b-(PMBC-co-PCL)n, developed from polyester and polycarbonate blends, that possessed shape memory and self-heal capabilities via a physical crosslinking system. The material demonstrated a significant tensile strength of 0.38 MPa and a tensile ratio of 1155.6%, highlighting its favorable mechanical properties. In addition, a conspicuous shape retrieval rate of 93% was showcased within 32.5 seconds at 37 o C. Remarkably, the affected area could be repaired proficiently with no irritation experienced during 6h at room temperature, which was indicative of an admirable repair percentage of 87.6%. Furthermore, these features could be precisely modified by altering the proportion of 5-methyl-5benzyloxycarbonyl-1,3-dioxane-2-one (MBC) and ε -caprolactone (ε-CL) to suit individual constraints. This innovative elastomer with exceptional shape memory and self-heal capabilities provides a solid basis and promising potential for the development of self-contracting intelligent surgical sutures in the biomedical field.